Using a standardised protocol was effective in reducing hospitalisation and treatment use in children with newly diagnosed immune thrombocytopenia. (11th May 2017) - Labrosse, R; Vincent, M; Nguyen, U‐P; Chartrand, C; Di Liddo, L; Pastore, Y
Abstract: Aim: Childhood immune thrombocytopenia (ITP) has been associated with low bleeding rates and a high frequency of spontaneous remission. Although current guidelines suggest that most patients are just observed, children still receive platelet‐enhancing therapies for fear of bleeding complications. We hypothesised that a standardised protocol with a step‐down approach would reduce hospitalisation and treatment use. Method: A retrospective chart review was performed on patients diagnosed with acute ITP between January 2010 and December 2014, before (n = 54) and after (n = 37) the standardised protocol, which was introduced in January 2013. Management and events during the first 3 months following diagnosis were recorded. Results: The protocol resulted in a 34% decrease in the hospitalisation rate (p < 0.001) at diagnosis. Prednisone treatment duration at diagnosis was also significantly reduced (13.1 versus 5.8 days, p = 0.004). Children over 3 years of age were 3.8 times less likely to be hospitalised (95% CI 1.94–7.61) and 2.3 times less likely to receive treatment (95% CI 1.2–4.3). There was no difference in the rate of persistent ITP (38% versus 30%, p = 0.43) or serious bleeding complications (7% versus 5%, p = 0.70). Conclusion: Our ITP management protocol significantly reduced hospitalisation rates and length of prednisone treatment without any increase in disease complications. Abstract :